Asymptotics of Polynomials Orthogonal with respect to a Logarithmic Weight - Conway, T.O.; Deift, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
In this paper, we compute the asymptotic behavior of the recurrence coefficients for polynomials orthogonal with respect to a logarithmic weight w(x)dx = log(2k/(1 - x))dx on (-1,1), with k > 1, and verify a conjecture of A. Magnus for these coefficients. We use Riemann-Hilbert/steepest-descent methods, but not in the standard way, as there is no known parametrix for the Riemann-Hilbert problem in a neighborhood of the logarithmic singularity at x = 1.